Cutaneous adnexal neoplasms in biopsy specimens processed in the Department of Pathology, University of Malaya - Jayalakshmi, P.; Looi, L.M. (Faculty of Medicine, University of Malaya, 1996)
A review of consecutive biopsies of adnexal tumours from 112 patients, received by the Department of Pathology, University of Malaya, over a 13-year period was undertaken. The age range of the patients was from 1 to 84 years, with a mean of 29.8 years. Thirty-three (32%) patients were under 20 years of age. There were 68 females with a male to female ratio of 1.0:1.5. In 105 cases (93.7%), the neoplasm was solitary. The tumour measured less than 2 cm in the largest dimension in 103 cases (92%). The common sites of occurrence were the head and neck region (59%) and extremities (25%). Neoplasms of hair follicle origin accounted for 63.4% (71 cases) of all lesions. Intra-tumour deposition of amyloid was noted in one of the 14 cases of trichoepithelioma.